Polypharmacy and Major Adverse Events in Atrial Fibrillation. Issue 6 (December 2022) - Tsagkaris, Christos; Papazoglou, Andreas S.; Kartas, Anastasios; Samaras, Athanasios; Moysidis, Dimitrios V.; Vouloagkas, Ioannis; Baroutidou, Amalia; Bekiaridou, Alexandra; Patsiou, Vasiliki; Chatzisolomou, Antreas; Panteris, Eleftherios; Karagiannidis, Efstratios; et al.
Abstract: Patients with atrial fibrillation (AF) often receive multiple medications daily. The purpose of this study was to examine the prognostic implications of polypharmacy in patients with AF. This is a retrospective post hoc analysis of 1113 AF patients, enrolled in a randomized trial during an acute hospitalization (MISOAC-AF, NCT02941978). The presence of polypharmacy (use of >4 drugs daily) was assessed at hospital discharge. Regression analyses were performed to identify clinical predictors of polypharmacy and compare the outcomes of patients with or without confirmed polypharmacy. The coprimary outcomes were all-cause and cardiovascular (CV) mortality. Among patients with polypharmacy, the difference in the risk of mortality was also assessed per each added drug as a numeric variable. Polypharmacy was found in 36.9% of participants. Dyslipidemia, coronary artery disease, lower left ventricular ejection fraction, and higher glomerular filtration rates were independent predictors of polypharmacy. Polypharmacy was an independent predictor for all-cause death (adjusted hazard ratio [aHR]: 1.29, 95% confidence interval [CI]: 1.01–1.64) and CV death (aHR: 1.39, 95% CI: 1.05–1.84). Among patients with polypharmacy, each additional concomitant medication was independently associated with a 4% increased risk of all-cause mortality (aHR = 1.04, 95% CI: 1.00–1.08) and a 5% increased risk of CV mortality (aHR = 1.05, 95% CI: 1.00–1.10). Polypharmacy was common among patients with AF hospitalized in a tertiary hospital and was incrementally associated with higher rates of mortality.